Modelling corporate income tax revenues in Latvia - Ozolina, Velga; Auzina-Emsina, Astra (Univerzita Pardubice, 2018)
The article is devoted to the issues of modelling and forecasting corporate income tax revenues in Latvia. Analysis of legal aspects and data shows that it is necessary to distinguish between advance payments (usually monthly payments) and final tax payments made in March, April or May. Following the usual practice, both identities and econometric equations are estimated for forecasting the corporate income tax revenues. Such factors as profit, private consumption price index, exports, wages, private consumption and investment are used as the factors along the tax rate. It is possible to use estimated monthly econometric equation for the short-term forecasting as it provides reasonably precise results and demands less assumptions as the other proposed models, but forecasts should be evaluated together with the results of identities. Estimated equations have to be applied together with the reliable models of influencing factors. The research findings are valuable for other countries as corporate income tax is a standard tax in fiscal system in all EU and other countries.
Keywords: corporate income tax revenues; tax revenues modelling; tax revenues forecasting; factors; Latvia; C51; C52; H25; H68